Educational policy and remote education in early childhood education in Fortaleza during pandemic time: experience report (Research, Society and Development, 2021)
The year 2020 surprised the world by the force and stormy Pandemic of Covid-19. In mid-March this year, the Coronavirus arrives in Brazil and the whole dynamic of life in society goes through great and necessary changes, adopting new ways of being and being in the world. The country has been facing several social, political, economic and cultural problems during this period, generating complex consequences, mainly in ensuring the subjective right to quality public education, as expressed in article 5 of the Law of Guidelines and Bases of National Education (LDBEN) 9,394 / 1996. Our proposal is to present an experience report on the remote education of early childhood education in Fortaleza in 2020, addressing the challenges and achievements of educational policy in a pandemic period. The first stage of basic education, as determined by article 29 of LDBEN 9.394 / 1996, defines that early childhood education focuses on the integral development of children up to 5 (five) years old, in its physical, psychological, intellectual and social aspects, complementing the action of the family and the community. The experience report chose to highlight the actions that were carried out in early childhood education in the municipal network of Fortaleza, in the period of social isolation, referring to the year 2020.